Engaging small firms in sustainable supply chains: responsible sourcing practices in the UK construction industry. (1st January 2012) - Glass, Jacqueline; Achour, Nebil; Parry, Tony; Nicholson, Ian
Responsible sourcing (RS) provides a means to manage sustainability objectives by procuring materials with a certified provenance and is demonstrated typically through an organisation's procurement policy, via purchasing decisions and practices. In the UK, the government requires that 25% of construction products shall be from RS schemes by 2012; major contractors are raising this target to 100% by 2015 for major commodities such as aggregates, metals, steel, concrete, bricks and glass. There is a lack of research on industry preparedness for RS, so this paper reports on an industry survey and interviews that set out to explore the scope of RS, its drivers, benefits and challenges. It shows that material suppliers are leading the way, and although specifiers, clients and major contractors can drive change in the supply chain, there is a problem with a lack of participation from small and medium enterprises (SMEs) which warrants further research.